Reconstructing the Concept of Sakinah Family in the Qur’an: A Maqāṣidī Tafsir Analysis of Contemporary Muslim Family Dynamics - Yuzaidi Yuzaidi; Winda Sari; Aris Munandar; Muh Yiddin; Iqbal Ubaidi Al-Lammushi (Universitas Muhammadiyah Bandung, 2025)
Contemporary Muslim families are increasingly confronted with complex social challenges arising from globalization, digital transformation, economic instability, shifting gender relations, and weakening emotional communication within households. In many Muslim societies, the concept of the sakinah family is frequently understood through normative and legalistic frameworks that emphasize formal obedience and patriarchal authority while paying limited attention to emotional well-being, ethical partnership, and contemporary social realities. This study aims to reconstruct the Qur’anic concept of the sakinah family through a maqāṣidī tafsir approach by integrating Qur’anic ethics with contemporary Muslim family dynamics. This research employs a qualitative library-based method using thematic Qur’anic interpretation (tafsīr mawḍū‘ī) and the framework of maqāṣid al-sharī‘ah. Primary data are derived from Qur’anic verses related to family ethics, while secondary data include classical and contemporary tafsir works, maqāṣid literature, and recent studies on Muslim family transformation. The findings reveal that the Qur’anic concept of the sakinah family extends beyond formal marital legality toward the realization of emotional tranquility, ethical communication, compassion, collaborative responsibility, and spiritual resilience. Through the maqāṣidī perspective, sakinah is reconstructed as a dynamic ethical framework grounded in the principles of maṣlaḥah, justice, reciprocity, and family welfare. The study also demonstrates that concepts such as qiwāmah, mawaddah, and raḥmah should be interpreted contextually in response to contemporary social realities rather than through rigid patriarchal understandings. Theoretically, this article contributes to the development of contemporary Qur’anic studies by demonstrating the relevance of maqāṣidī tafsir as a contextual and transformative interpretive approach. Socially, the study offers an ethical framework for strengthening emotional resilience, communication, and family harmony within contemporary Muslim societies.